Microcrystalline silicon solar cells with passivated interfaces for high open‐circuit voltage. Issue 4 (2nd February 2015) - Hänni, Simon; Boccard, Mathieu; Bugnon, Grégory; Despeisse, Matthieu; Schüttauf, Jan‐Willem; Haug, Franz‐Josef; Meillaud, Fanny; Ballif, Christophe
<x xml:space="preserve">Abstract</x> We introduce passivating hetero‐interfaces in single‐junction microcrystalline silicon (μc‐Si:H) solar cells. We investigate the effect of different i–n layer stacks in thin μc‐Si:H devices, in which recombination is significant at the interfaces as well as in the bulk material. By applying amorphous silicon passivating layers at the μc‐Si:H i–n interface, we show a device with a high open‐circuit voltage (Voc) of 608 mV, for a standard Raman crystalline fraction of the i‐layer (>50%). This Voc is the highest reported value for a state‐of‐the‐art μc‐Si:H device made by plasma‐enhanced chemical vapor deposition. We also report an efficiency of 9.45% for a solar cell with an absorber layer as thin as 650 nm on an area greater than 1 cm2, and show with a simple crystalline silicon model that for such thin μc‐Si:H devices or μc‐Si:H devices with a very high bulk‐material quality, well‐mastered interfaces and doped layers are of paramount importance for high efficiency.